Clathrin mediates both internalization and vesicular release of triggered T cell receptor at the immunological synapse - Kvalvaag, A; Valvo, S; Céspedes, PF; Saliba, DG; Kurz, E; Korobchevskaya, K; Dustin, ML (National Academy of Sciences, 2023)
Ligation of T cell receptor (TCR) to peptide-MHC (pMHC) complexes initiates signaling leading to T cell activation and TCR ubiquitination. Ubiquitinated TCR is then either internalized by the T cell or released toward the antigen-presenting cell (APC) in extracellular vesicles. How these distinct fates are orchestrated is unknown. Here, we show that clathrin is first recruited to TCR microclusters by HRS and STAM2 to initiate release of TCR in extracellular vesicles through clathrin- and ESCRT-mediated ectocytosis directly from the plasma membrane. Subsequently, EPN1 recruits clathrin to remaining TCR microclusters to enable trans-endocytosis of pMHC-TCR conjugates from the APC. With these results, we demonstrate how clathrin governs bidirectional membrane exchange at the immunological synapse through two topologically opposite processes coordinated by the sequential recruitment of ecto- and endocytic adaptors. This provides a scaffold for direct two-way communication between T cells and APCs.